Openness, Efficiency and Technology: An Industry Assessment. (3rd January 2013) - Christopoulos, Dimitris; McAdam, Peter
Abstract Most trade and macroeconomic models imply positive impacts on the economy from greater openness. And a key factor linking openness and progress is the efficiency with which resources are used. Empirically, however, the efficiency impacts of trade have been ambiguous. Using a stochastic frontier analysis, we examine the impact of openness on technical (in)efficiency for a sample of OECD economies. Unlike the bulk of related studies, we work at the industry level. Given recent debates, we additionally examine whether Information and Communication Technologies (ICT) expenditures impact openness and efficiency. We establish the elasticity of openness with respect to (in)efficiency; TFP and Scale Economies; and Technical Inefficiency across countries and sectors. Both openness and ICT usage have robustly positive impacts on efficiency. Our results shed light on the impact of, spillovers between, and heterogeneity across countries and industries from, increasing openness interacted with the use of advanced technologies.